Solid Pseudopapillary Carcinoma of the Pancreas in a Child: Surgical Treatment and Postoperative Complications ‒ A Case Report - Šimkūnaitė, Kotryna; Lukošiūtė-Urbonienė, Aušra; Vanagas, Tomas (Lietuvos chirurgija, 2025)
Solid pseudopapillary neoplasm (SPN) of the pancreas is a rare pancreatic neoplasm with low malignant potential, most commonly occurring in young patients. Although this condition is more frequently diagnosed in adults, it accounts for approximately 8–12% of all pancreatic tumors in children. The diagnosis of SPN is challenging due to its often asymptomatic nature, with tumors typically remaining undetected until they reach a considerable size of 5–7 cm. Furthermore, some patients may present with nonspecific symptoms, which can complicate the diagnosis. The treatment of choice is formal pancreatic resection, during which the tumor is radically removed. Although the long-term prognosis for SPN is generally favorable, postoperative complications such as pancreatic fistulas are common. Treatment of these complications may require antibiotic therapy and drainage of peripancreatic fluid collections. This article presents a clinical case in which a 15-year-old girl was incidentally diagnosed with a solid pseudopapillary carcinoma located in the tail of the pancreas, and underwent formal pancreatic resection. We discussed the importance of close postoperative monitoring and the potential causes of postoperative complications.